Attitudes of business leaders and professional ecologists toward corporate social funding of environmental conservation - G. R. Preston; R. F. Fuggle; W. R. Siegfried (South African Journal of Business Management, 1990)
A study of South Africa's business leaders and professional ecologists reveals strong support for corporate social funding. However, the average level from after-tax profits considered appropriate for corporate social funding by business leaders (3%) is appreciably lower than the ecologists' average of 14,5%. Both business leaders and professional ecologists believe that environmental conservation deserves greater financial support than it currently receives. Education is rated as the most worthy sphere for corporate social funding by both groups. Whereas ecologists rate job creation and housing as of equal concern to environmental conservation, and health and welfare of lesser concern, business leaders rate them all as of greater worthiness for funding than environmental conservation. Both groups regard rural development as a less important target for funding (although the ecologists place a greater emphasis on this sphere than the business leaders do), and deem the arts and sport to be of low priority. The business leaders' preferences for funding follow their perceptions of the priority Issues facing South Africa at present, whereas ecologists believe that such funding should be selective, rather than effectively being a back-up for government responsibilities. The expressed concern for support of population control, acknowledged to be the most serious conservation Issue in South Africa at present, is offset by the low level of actual corporate support for this Issue. Business leaders, in particular, claim that corporate social funding of environmental conservation is backed by shareholders.
Keywords: 650